2014
DOI: 10.1038/emm.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

MiR-152 suppresses the proliferation and invasion of NSCLC cells by inhibiting FGF2

Abstract: MicroRNAs (miRNAs) regulate the proliferation and metastasis of cancer cells. Here, we showed that miR-152 was downregulated in non-small-cell lung cancer (NSCLC) tissues and cell lines. Overexpression of miR-152 suppressed cell proliferation and colony formation and also limited migration and invasion. Fibroblast growth factor 2 (FGF2) was confirmed as a direct target of miR-152. FGF2 knockdown suppressed cell proliferation, colony formation, migration and invasion, whereas FGF2 overexpression partially rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 35 publications
1
52
1
1
Order By: Relevance
“…In these reports, overexpression of miRNAs targeting PTEN has been considered a contributing factor for tumor development (Huse et al, 2009). However, as our study indicated, miR-152 is also a potential regulator of PTEN; most previous reports have indicated that miR-152 acts as a tumor suppressor by targeting proteins other than PTEN (Cheng et al, 2014;He et al, 2015;. Therefore, although our data suggest a protective function of miR-152 during hypoxiainduced apoptosis in primary microvascular endothelial cells, the miR-152-PTEN relationship and its effects on the development and progression of cancer requires further investigation.…”
Section: Discussioncontrasting
confidence: 38%
“…In these reports, overexpression of miRNAs targeting PTEN has been considered a contributing factor for tumor development (Huse et al, 2009). However, as our study indicated, miR-152 is also a potential regulator of PTEN; most previous reports have indicated that miR-152 acts as a tumor suppressor by targeting proteins other than PTEN (Cheng et al, 2014;He et al, 2015;. Therefore, although our data suggest a protective function of miR-152 during hypoxiainduced apoptosis in primary microvascular endothelial cells, the miR-152-PTEN relationship and its effects on the development and progression of cancer requires further investigation.…”
Section: Discussioncontrasting
confidence: 38%
“…For Trim72 (an E3 ubiquitin ligase) and Fga (the extracellular matrix protein fibrinogen involved in blood clot formation), there is little information associating them to metastasis or cancer. Studies have shown that miR-152 and miR-345 are associated with cancer and metastasis (Cheng et al, 2014; Tang et al, 2011). FGF2 and BAG3 , which promote metastasis, were predicted targets of miR-152 and miR-345 , thus loss of these microRNAs may lead to acceleration of metastases likely due to de-repression of these genes (Cheng et al, 2014; Tang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…39 We suppresses cell proliferation and invasion of non-small-cell lung cancer by inhibiting FGF2. 61 Considering the up-regulation of miR-152 in hiPSCs-SLE, it would be interesting to investigate whether the AA-H 2 O 2 condition may suppress their proliferative potential through a similar mechanism previously described by Cheng et al…”
Section: Discussionmentioning
confidence: 88%